High-risk extracorporeal membrane oxygenation in immunocompromised children with acute respiratory failure: a retrospective cohort study - Belevskaia, Liudmila; von Borell, Florian; Baumann, Ulrich; Beier, Rita; Köditz, Harald (Frontiers in Oncology, 2025)
BackgroundExtracorporeal membrane oxygenation (ECMO) is increasingly being utilized in pediatric patients with severe respiratory failure, extending its use to high-risk patients, including those who are immunocompromised. Despite its growing application, reports on outcomes and prognostic factors in this specific population are scarce, highlighting a gap in our understanding.MethodsThis retrospective cohort study analyzed the outcomes of 19 immunocompromised pediatric patients who received ECMO for respiratory failure at our institution between 2006 and 2023. Patients were classified as immunocompromised due to conditions such as cancer, hematopoietic cell transplantation (HCT), primary immunodeficiency or receiving immunosuppression for a chronic (auto-) inflammatory disease. Data on patient demographics, baseline laboratory and ventilation parameters were collected and compared between survivors and non-survivors.ResultsThe median age of patients was 12.1 years, and the majority suffered from infectious pneumonia leading to respiratory failure. The median duration of ventilation before ECMO was 5 days, and ECMO support lasted a median of 19 days. The hospital mortality rate in this cohort was 74% (14/19). All patients who had undergone HCT or a primary immunodeficiency did not survive. Non-survivors exhibited significantly higher median C-reactive protein levels and more bleeding complications. Other laboratory and respiratory parameters, as well as vasopressor requirements, pSOFA, and P-PREP scores, were similar across survivors and non-survivors.ConclusionThe treatment of immunocompromised pediatric patients with ECMO for respiratory failure presents notable challenges. This study highlights the complexity of predicting outcomes in this group, as traditional laboratory and respiratory parameters were not distinctly different between survivors and non-survivors. These findings indicate a need for continued research and nuanced clinical approaches to improve care and outcomes in this vulnerable population.